2006
DOI: 10.1111/j.1399-6576.2006.00940.x
|View full text |Cite
|
Sign up to set email alerts
|

Clonidine in paediatric anaesthesia: review of the literature and comparison with benzodiazepines for premedication

Abstract: Background:  Children undergoing anaesthesia and surgery can experience significant anxiety and distress during the peri‐operative period, but whether routine premedication is necessary is currently debated. Benzodiazepines are the most frequently used drugs as premedication in paediatric anaesthesia. In the US, 50% of young children undergoing surgery receive premedication and midazolam is the most frequently used drug in this context (1). Nishina and coworkers (2) concluded in a review article in 1999 that c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
82
0
2

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(97 citation statements)
references
References 95 publications
2
82
0
2
Order By: Relevance
“…impairment, amnesia, and respiratory depression. 4,5 New drugs, such as the α 2 -agonists, have emerged as alternatives for iv sedation. Dexmedetomidine is a highly selective α 2 -adrenoceptor agonist that has sedative and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…impairment, amnesia, and respiratory depression. 4,5 New drugs, such as the α 2 -agonists, have emerged as alternatives for iv sedation. Dexmedetomidine is a highly selective α 2 -adrenoceptor agonist that has sedative and analgesic effects.…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Its beneficial effects in adult are well documented and this has encouraged the study of this drug in paediatric anaesthesia setting as well.…”
Section: Introductionmentioning
confidence: 99%
“…Although amnesia is considered an advantage by some authorities, it has also been regarded as a possible disadvantage by others (15) . Clonidine (16) , an α2-agonist, has been suggested as another option for premedication in children and previous studies have shown it to be equally as effective as midazolam. Oral (17,18) clonidine premedication has also been shown to reduce the incidence of sevoflurane induced emergence agitation.…”
Section: Introductionmentioning
confidence: 99%